Atributos físicos do solo conduzidos sob escarificação mecânica, biológica e plantio direto: influência na produtividade biológica das culturas - Haskel, Maiara Karini (2020)
The areas conducted under no-tillage have been facing difficulties related to the compacted layer, interfering in the root growth of plants, with emphasis on times with reduced water regime, limiting the productive potential of annual crops. In this way, we sought to evaluate practices adopted to mitigate soil compaction in the Southwest region of Paraná, by mechanical and biological interference, using cover crops, and the respective effects of management on soil attributes, cover crops and corn crop. The experiment was implemented in the UTFPR experimental area, Câmpus Dois Vizinhos, in 2015, consisting of 5 soil tillage systems: PD - no-tillage; PDEa- No-tillage scarified annually; PDEi- Scarified no-tillage with 3-year interval; PDPMa- No-tillage with minimum preparation annually; PDPMi- No-tillage with minimum tillage with a 3-year interval. The PDE preparations use a conventional fin, while the PDPM used a scarifier with greater spacing between rods and a breaker roller, being performed before the cover crops. The cover plants used in succession to the corn crop are: oats, common vetch, forage turnip and consortium of the 3 species, composing a 5x4 factorial experiment, conducted in random blocks, with three replications. Density (Ds), Total porosity (Pt), Macroporosity (Ma), Microporosity (Mi), Soil resistance were evaluated as parameters to determine the changes caused by the first cycle of the experiment and subsequent return of the preparations in the areas with intervals. root penetration (RP) over two agricultural harvests, water infiltration in the soil, soil cover rate per cover plant, straw and exposed soil after preparation, production of dry matter (MS) from cover plants, Carbon (C) and Nitrogen (N) content of plant tissue in cover crops, MS production and corn crop productivity. Soil preparation and cover crops did not influence the variables Ds, Ma, Mi, Pt, however soil scarification was efficient in reducing the PR of the 0.10-0.20 m layer, when compared to the PD. For water infiltration in the soil, the area conducted by the PDPMa provided a stable infiltration of about 360 mm h-1, while the other preparations showed infiltration below 90 mm h-1. For the variable soil cover rate, there was a significant interaction between soil tillage and cover plants, so that soil tillage showed greater soil exposure due to the incorporation of straw, while oats and turnip stood out among plants for soil cover by plants and for higher MS production. MS production and corn and buckwheat yield were not affected by soil management and cover crops, with an average yield of buckwheat crop of 0.93 Mg ha-1 and about corn 10,3 and 8,7 Mg ha-1 for the 2018/2019 and 2019/2020 harvest. Soil preparation influenced the RP and water infiltration in the soil, but did not influence the productive performance of the plants.